Refractive index matching for high light transmission composite systems. (October 2018) - Keaney, Erin; Shearer, John; Panwar, Artee; Mead, Joey
Transparent optical polymer/filler systems can be produced into complex shapes for a range of applications, such as lenses, shields, and containers. This work used refractive index liquids as a model for polymer matrices to investigate the degree of refractive index match required to maintain high transmission in an inorganic-filled polymer system (cubic calcium fluoride with particle size of 1 to 5 µm) over the visible spectrum. It was determined that in order to achieve a transparent composite (>85% transmission with 10 mm pathlength) with this filler (using literature reported dispersion data), the materials must have a refractive index match within ±0.007 for 1.6 vol.% loading. With a loading of 3.1 vol.%, the matching range required was reduced to approximately ±0.002.